Phenotypic Variability of Brachiaria Decumbens After Exposure to Gamma Irradiation - Hussin, Ghazalli (2003)
Brachiaria decumbens (Signal grass) has been used for many years as grazing pastures for ruminants. Its toxicity to small ruminants is the main limitation to utilization of this grass. Many researchers have reported several methods to control or alleviate this problem. Since there is a potential to use mutagenesis techniques to obtain variability of the plants, the objective of this study is to observe the phenotypic variability of Signal grass after mutagenic induction with gamma radiation. Further studies can be conducted to make a selection of variants which are free from toxicity. Brachiaria decumbens seeds were irradiated at doses of 1 00, 200, 300, 400, 500, 600, 700, 800 and 900 Gy to determine the appropriate doses for mutagenic treatments of the grass. The results showed that, B. decumbens seeds were less sensitive to gamma ray than most other species and the LD50 was found to be between 800 to 900 Oy. In order to observe the effects of gamma radiation on phenotypic variability of the grass, the grass seeds were exposed to 900 Oy gamma radiation. Results showed that gamma radiation at 900 Oy increased variability in morphological characteristics and nutrient contents and an obvious phenotypic mutant was detected. There were significant increases in variabilities of morphological characters (tiller numbers, leaf length, leaf width, leaf weights, stem weights., leaf-to-stem ratio and internode lengths) and nutrient contents (Crude Protein, Ether Extract, Crude Fibre, Acid Detergent Fibre, Neutral Detergent Fibre and Ash) among the treated plants. There was also a positive skew of the frequency distribution curve for the treated plants to the right, indicating that mutagenic radiation can cause increased variability, which allows greater selection potential for desired characteristics. DNA Polymorphism in the mutant cannot be detected through RAPD. The mutant showed significantly higher leaf width, leaf-to-stem ratio and crude protein compared to control plants.